MENINGKATKAN HASIL BELAJAR SISWA MELALUI PENERAPAN MODEL PEMBELAJARAN COOPERATIVE LEARNING DALAM PEMBELAJARAN KETERAMPILAN SULAMAN DI KELAS VII-1 SMP MUHAMMADIAH 6 PADANG - ARIYANI, Drs. Erwin, M.Sn, Dra. Ernis, M.Pd (Serupa The Journal of Art Education, 2014)
This research aims to determine the improvement of student learning outcomes in subjects embroidery in class VII-1 junior Muhammadiah 6 Padang through the implementation of cooperative learning teaching model. Data were collected using the research instruments and observation sheets against 35 students in two cycles. Data were obtained and analyzed using percentages. The results showed that the average value of 65.62 pre cycle rose to 70.61 in the first cycle, and increased again to 77.6 in the second cycle. Our findings suggest that the model of cooperative learning can improve learning outcomes Students learn the embroidery skills of Class VII-1 junior Muhammadiah 6 Padang. It is recommended to teachers sutudi same field or allied to implement this method in the learning.Key words: Cooperative Learning, Peningkatan Hasil Belajar.